Parodia, intertextualidad y sátira en la narrativa policial de Lorenzo Lunar Cardedo - Gómez-de-Tejada, Jesús (Studia Romanica Posnaniensia, 2020)
Detective fiction as parodic reformulation of genre’s defining patterns has a long history in the Latin American tradition: Borges, Bioy Casares, Soriano, Levrero, Ibargüengoitia, etc. Besides, the evolution of Latin American detective genre has always been characterized by a progressive focalization in the social aspects over the detective story line which has served as a mask to depict in a critical way the flaws of the region’s societies and governments. In nowadays Cuba it could be highlighted the crime narrative of parodic slant by Lorenzo Lunar Cardedo. Among the major features of Lunar Cardedo’s style there are the marginal atmospheres, the stylization of popular speech, the intertextuality, the humor, the parody, and the social criticism. This article focuses on the parodic, intertextual and satiric aspects of his work, particularly discernible in the novel Proyecto en negro (2013), in which the author emphasizes – in opposition to the official discourse – the perpetuation of corrupt, chauvinist, racist, and homophobic behaviors in contemporary Cuba, while relaxing the genre formula limits in order to follow a much more irreverent path within the new Latin American detective fiction.